Enzymatic Transesterification of Rubber Seed Oil Using Rhizopus Oryzae Lipase. (2016) - Vipin, V.C.; Sebastian, Jilse; Muraleedharan, C.; Santhiagu, A.
Abstract: Biodiesel production from non-edible rubber seed oil with high free fatty acid (FFA 26%) content was investigated. Rhizopus Oryzae Lipase in the form of free powder was used as catalyst. The effect of reaction parameters such as catalyst concentration, reaction duration, pH of the reaction mixture, type of acyl acceptors used and oil to acyl acceptor molar ratio were studied. Ethyl acetate gave better results in comparison with methanol as acyl acceptor. A maximum conversion of 33.3% was obtained when ethyl acetate was used, at a molar ratio of 1:11 and catalyst concentration 10 (w/w) % of oil after 24hours. In case of methanol, maximum conversion was 31% at a molar ratio of 1:4 and catalyst concentration of 15(w/w) % of oil after 48hours. Variation in pH did not show any significant change in percentage of conversion.